2022
DOI: 10.3389/fendo.2022.930756
|View full text |Cite
|
Sign up to set email alerts
|

Myoinositol in Autoimmune Thyroiditis

Abstract: Myoinositol (Myo) is an isoform of inositol, a cyclic polyol with 6 hydroxyl groups. Myo is mainly derived from dietary intake while its endogenous production is generated from glucose by enzymatic reactions. Moreover, Myo is also synthesized de novo by catabolism of phosphatidylinositol (PI), phosphoinositides (PIP), and inositol phosphates (IP). Myo has a determinant role in thyroid function and autoimmune diseases as it regulates iodine organification and thyroid hormone biosynthesis by the formation of hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…Some intervention studies performed in adult non-pregnant subjects showed that a myo-inositol (in association with selenium) supplementation was able to decrease TSH and anti-thyroid antibodies titers in patients with chronic autoimmune thyroiditis [117]. Nevertheless, these results should be confirmed by larger RCTs [116,118].…”
Section: Myo-inositolmentioning
confidence: 96%
“…Some intervention studies performed in adult non-pregnant subjects showed that a myo-inositol (in association with selenium) supplementation was able to decrease TSH and anti-thyroid antibodies titers in patients with chronic autoimmune thyroiditis [117]. Nevertheless, these results should be confirmed by larger RCTs [116,118].…”
Section: Myo-inositolmentioning
confidence: 96%
“…AITD patients overexpress certain inflammatory factors through exosomes, leading to an increase in serum TPOAb and TgAb levels, thereby affecting the occurrence and development of AITD ( 49 , 50 ). Myoinositol (Myo) has also been found to have beneficial effects on AITD ( 51 ). The emergence of AITD is accompanied by changes in various pathogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Myo is involved in the TSH signaling pathway; thus, depleted levels of Myo may cause the pathogenesis of thyroid diseases such as hypothyroidism ( 187 ). It has been observed that TSH levels significantly decreased in patients with subclinical hypothyroidism, with or without autoimmune thyroiditis, after treatment with Myo in combination with selenium ( 201 , 202 ). Studies of patients with Hashimoto’s thyroiditis and subclinical hypothyroidism showed that supplementation of Myo and selenomethionine significantly decreased TSH, TPOAb, and TGAb concentrations, while simultaneously increasing thyroid hormones levels and restoring euthyroid state in patients with autoimmune thyroiditis ( 203 , 204 ).…”
Section: Nutritional Antioxidants and Thyroid Diseasementioning
confidence: 99%